Channel Complementarity or Displacement? Theory and Evidence from a non-Western Election Context. Issue 4 (2nd October 2019) - Neyazi, Taberez Ahmed; Kumar, Anup; Dutta, Mohan J.
Abstract : The ubiquity of the Internet in all domains of human communication merits a renewed focus on the channel complementarity and displacement hypotheses, not least because social media enables the sharing of information beyond information-seeking. The present study draws on a cross-sectional survey, conducted during the 2014 national election in India. Findings indicate that exposure to traditional media significantly predicted exposure to social media. Sharing text messages, discussing the campaign face-to-face, listening to the radio, and campaign interest predicted sharing information on social media. The findings provide important insights into channel complementarity theory, demonstrating the positive relationship between traditional and new media-based exposure and information-sharing.